The Implementation Of English Teaching-Learning ProcessFor The Eleventh Grade Students By Using Moving ClassAt SMK Negeri 1 Klego In 2012/2013 Academic Year - Agustina, Agustina, Drs. Djoko Srijono, M.Hum, Siti Fatimah, S.Pd, M.Hum (2013)
This research is aimed at describing: : 1) the implementation of moving class, 2) the obstacles encountered in the implementation of moving class, and 3) the attempt conducted in coping with the obstacles encountered. In this research is descriptive research as an approach to collect and analyze the data. The object of this research is the implementation of english teaching learning process by using moving class at SMK Negeri 1 Klego in 2012/2013 academic year. The method of colleting data is conducted by doing: observation, interview, and document analysis. The result of this research show that the implementation of moving class. The implementation of moving class, encounters several obstacles including: there are no locker for storing the students bag, less effective time, less fulfilled facilities of ICT-based learning, many teachers have not operated laptop or LCD, the lack of socialization from the school to the students. The attempts the SMK Negeri 1 Klego has conducted to cope with such obstacles are: the school will make locker for storing the students bag, it fulfill gradually the facilities necessary in implementing the moving class.